Peran Dinas Pertanian dalam Pengelolaan dan Pengembangan Perkebunan di Kabupaten Jember - Purnama Sari, Retno; Zulfikar Ahmad Alfarizi; Rudi Indrawan (Program Studi Ilmu Tanah, Fakultas Pertanian, Universitas Jember, 2025)
The agriculture and plantation sectors play a strategic role in the Indonesian economy, especially in food security and export of superior commodities. Jember Regency is one of the regions with a rapidly growing plantation sector, especially in commodities such as tobacco, coffee, cocoa, and rubber. The success of this sector is supported by favorable geographical conditions and the application of modern agricultural technology. However, challenges such as land conversion, climate change, and market price fluctuations are still major obstacles. This study aims to analyze the role of the Agriculture Office in the management and development of plantation crops in Jember Regency. The research method was conducted through a 45-day internship at the Food Crops, Horticulture, and Plantation Office of Jember Regency. The study included data collection on crop productivity, farmer group assistance, and visits to tobacco factories to understand the dynamics of production and marketing. The results show that the Jember Plantation Office has a crucial role in policy formulation, technical assistance, and supervision of sustainability-based programs. The agency also encourages technological innovation, provides subsidies, and agricultural equipment assistance to improve the competitiveness of plantation products. However, various obstacles such as dependence on exports, global competition, and limited marketing are still challenges that require synergy between the government, farmers, and the private sector.